Scale up de processo de biodegradação do óleo diesel em água do mar por candida lipolytica UCP0988. - Nobrega, Hamilton Felix (2016)
Strategy scale-up in two stages was adopted to the process of biodegradation diesel Candida lipoytica UCP 0988 in sea water, in 2.8-L Fernbach flasks and in 5-L bench bioreactor to study the effects of agitation, aeration and inoculum concentration on diesel oil degradation process by Candida lipolytica UCP 0988 in sea water. 22 full factorial design was carried out on a scale of Fernbach flasks, to investigate the effects of the initial biomass concentration (inoculum) and agitation on the biomass concentration, pH, surface tension and the rate of biodegradation of total hydrocarbons after 216h. Stirring influence the concentration of dissolved oxygen, which in turn affected the growth and hydrocarbon biodegradation. In both scales, the yeast used diesel oil, B7 type, 10% as a sole source of carbon and energy, degraded partially or totally aliphatic, branched and unbranched hydrocarbons and aromatic hydrocarbons. The latter showed increased resistance to biodegradation. Biofilm formation contributed to increase hydrocarbon degradation efficiency. Scale 5L bioreactor after 9 days of diesel oil biodegradation process were synthesized 7.2 g/L cell mass in metabolic liquid with pH, salinity, surface tension and emulsifying emulsions activities with n-hexadecane, diesel oil and corn oil, respectively equal to 3.3; 47%, 38.36 mN / m 4,416 UEA; 4,409 UEA and 4,024 UEA. It was also verified biodegradation of approximately 67% of the hydrocarbon peaks resolved by gas chromatography / mass spectrometry. The scale-up strategy adopted was effective and can be used in the scale up process to larger scales.